Albanian Poetry Emerging from the Aftermath of the 1999 Kosovo War: Memory, Trauma, Revolt - Rogova Gaxha, Blerina (Journal of war and culture studies, 2024)
This article explores the memory of war, trauma, and revolt in Albanian poetry emerging from the aftermath of the 1998–99 Kosovo War. It focuses on constructing Kosovo Albanian post-war poetry and asks about the avenues of literary representation of war. It examines the work of Xhevdet Bajraj, Arben Idrizi and Halil Matoshi, focusing on the subjects’ positions – exile and national victimhood in the case of Bajraj; critique of violence in the case of Idrizi; disillusion and trauma in the case of Matoshi. The article also finds that Kosovo's post-war literature stands in a broader framework of the literature from ex- Yugoslav republics, providing a geographical and cultural background to war poetry. The view and interpretation of the literary response to the Kosovo War aims to highlight poetry that keeps memory about the war alive, as well and explores the impact of war, to protest against violence and domination.